2022
DOI: 10.4266/acc.2021.01193
|View full text |Cite
|
Sign up to set email alerts
|

Brain-lung interaction: a vicious cycle in traumatic brain injury

Abstract: The brain-lung interaction can seriously affect patients with traumatic brain injury, triggering a vicious cycle that worsens patient prognosis. Although the mechanisms of the interaction are not fully elucidated, several hypotheses, notably the "blast injury" theory or "double hit" model, have been proposed and constitute the basis of its development and progression. The brain and lungs strongly interact via complex pathways from the brain to the lungs but also from the lungs to the brain. The main pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
1
26
0
5
Order By: Relevance
“…We agree with Chacón-Aponte et al [ 1 ] that in patients with an acute traumatic head injury, altered pulmonary function is a frequent complication. NPE is a probable early contributor to the pulmonary dysfunction that occurs in patients suffering from acute head injuries.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…We agree with Chacón-Aponte et al [ 1 ] that in patients with an acute traumatic head injury, altered pulmonary function is a frequent complication. NPE is a probable early contributor to the pulmonary dysfunction that occurs in patients suffering from acute head injuries.…”
supporting
confidence: 93%
“…We read with immense interest the recent published narrative review by Chacón-Aponte et al [ 1 ] which concluded that brain-lung interactions can affect patients with traumatic brain injury (TBI). This interaction leads to a cruel cycle that aggravates patient prognosis.…”
mentioning
confidence: 99%
See 3 more Smart Citations